2020
DOI: 10.1097/sle.0000000000000876
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Surgery for Colorectal Cancer in Super-Elderly Patients: A Single-Center Analysis

Abstract: Background: Super-elderly patients with colorectal cancer are being encountered with increasing frequency in Japan. Laparoscopic surgery is considered a less invasive surgery in these patients; however, it is difficult to conduct controlled clinical trials in this super-elderly population. This study assessed the feasibility and safety of laparoscopic colorectal surgery in patients over 85 years old.Materials and Methods: Open and laparoscopic surgeries for colorectal cancer in super-elderly patients (aged 85 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Laparoscopic technology has been widely used in the treatment of colorectal cancer [ 11 13 ]. Compared with traditional open surgery, laparoscopic surgery has minimally invasive advantages such as less trauma, less postoperative pain, and faster recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic technology has been widely used in the treatment of colorectal cancer [ 11 13 ]. Compared with traditional open surgery, laparoscopic surgery has minimally invasive advantages such as less trauma, less postoperative pain, and faster recovery.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is supported by research from Vallribera Valls et al [ 14 ] who demonstrated that laparoscopic approaches in those over 85 are not associated with an increase in morbidity or length of stay. This is also mirrored by more recent studies of Ueda et al [ 15 ] and Hashida et al [ 16 ], both of whom have demonstrated laparoscopic surgery in the elderly population to be feasible, safe and have equitable outcomes to those in younger age brackets.…”
Section: Discussionmentioning
confidence: 66%
“…The super elderly group constitutes a special population, which is constantly increasing (1,5)(1,5)(1,5)(1,3), and deserves specialized studies due to their characteristics [ 18 , 19 ]. Benign biliary pathology is not the only exception and complications associated to cholelithiasis and age should be taken into account [ 20 ].…”
Section: Discussionmentioning
confidence: 99%